A sociedade carioca da Belle Époque nas páginas do nas páginas do Fon-Fon! - Zanon, Maria Cecilia [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
A revista Fon-Fon!, periódico que circulou na primeira metade do século XX, é um importante documento no que concerne ao registro da vida socio-cultural do Brasil durante a Belle Époque. O periódico espelhava o esnobismo carioca, fazia crítica, apresentava flagrantes e tipos do set da cidade, com muitas fotografias, ilustrações, literatura e excelentes charges políticas e sociais da sociedade do Rio de Janeiro. Este estudo visa mostrar a importância que esse periódico ocupou na representação do caráter da elite carioca da Belle Époque.

The Fon-Fon! Magazine, periodic that circulated in the first half of XX century, it is an important document with respect to the register of the sociocultural life of Brazil during the Belle Époque. The periodic showed the Carioca snobbish, made criticism, presented instants and types of the set of the city, with many photographs, excellent illustrations, literature and social charges, political charges of the society of Rio de Janeiro. This study it aims at to show the importance that this periodic charges occupied in the representation of the character of the Carioca elite of the Belle Époque
The carioca society of the belle époque on the pages of Fon-Fon! Magazine
Keywords: Fon-Fon Magazine; belle époque; french sociocultural influence; Revista Fon-Fon; belle-époque; influência sóciocultural francesa